Photo album - organizing photographs, understanding aesthetic - Chua, Jie Hong. (2011)
Data Mining is an analytic process of analyzing and exploring new patterns, from a large data set. This discovery of patterns and viewpoints of behavior which were previously unnoticed, will allow the researched data to be used in prediction and for application to businesses, or for finding out the relationships between given data sets.